24-hour movement behaviours and mental health in non-clinical populations: A systematic review. - Rachel Dale; Teresa O'Rourke; Barbara Nussbaumer-Streit; Thomas Probst (PLoS ONE)
The 24-hour movement guidelines consider movement behaviours (sleep, exercise, sedentary time) together within the frame of our 24-hour limit to provide recommendations on how a physically healthy day should look. There is increasing evidence that daily movement behaviours are associated with mental health. However the research into the relationship between 24-hour-movement and mental health, particularly in adults, is still to be systematically reviewed. The aim of this systematic review was to synthesise the current state of knowledge regarding movement behaviours and mental health in non-clinical child, adolescent and adult samples. systematic literature search of PubMed, Scopus and Embase was conducted in 2022, and updated in 2024. The review was preregistered (PROSPERO: CRD42022312717). Due to heterogeneity of methods and analyses, narrative synthesis of the results was employed. Of 103 eligible studies, one was a randomised controlled trial and the remainder were observational. In children 19/27 studies (70%) found at least one significant positive relationship between movement behaviour and mental health, in adolescents 38/41 (93%) and in adults 41/46 (89%). Certainty of evidence was low. More controlled studies are needed to make causal conclusions, but it is evident that the composition of movement behaviours is associated with mental health, and these associations may be differentially manifest in different age groups. This has implications for public health and mental health campaigns.